التدريس عن بعد أثناء جائحة كوفيد-19 لدى محاضري الكلية الإسلامية التكنولوجية العالمية بينانج: REMOTE TEACHING DURING THE COVID-19 PANDEMIC AMONG THE LECTURERS OF PENANG INTERNATIONAL ISLAMIC TECHNOLOGICAL COLLEGE - Abdul Aziz, Nur Farhana; Ishak, Nor Asniza; Yakob, Nooraida (Journal of Islamic Educational Research, 2021)
The world was shocked by the emergence of the Covid-19 virus. This situation affected the entire country, including universities and educational institutions. According to UNESCO reports, more than 1.5 billion students in about 165 countries have been affected by the closure of schools and campuses. As a result, schools, colleges, and universities had to switch to online learning. All parties have taken proactive steps by conducting online classes as well as the International Islamic Technological College Penang. This research aims to know the lecturers' strategies in carrying out the teaching process during the pandemic, their challenges, including technical knowledge and facilities available in college, and how they deal with these challenges. The paper employs qualitative approach where the researcher conducts interviews with the lecturers. In addition, this paper seeks to find out the effectiveness of online teaching during the Movement Control Order period. Among the problems that lecturers face is a lack of skills in conducting online classes and taking longer time to prepare teaching materials. The result also indicated that the lecturers lack competence in integrating technology into teaching. Although they encountered problems, the lecturers tried to learn from their colleagues and some of the lecturers were able to create a YouTube, channel and attend webinars.